Phytoextraction and Cd Allocation to the Stem of Woody Species Used in Cacao Agroforestry - L. Carvalho, Fabricio E.; Montenegro, Andrea C.; Escobar Pachajoa, Laura D.; Rojas Molina, Jairo; Camacho Diaz, Jorge E.; Rengifo Estrada, Gersain A. (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Global cacao production, primarily led by African countries, is facing a crisis, which presents growth potential for South American countries like Colombia, Peru, and Ecuador. However, a significant challenge for these countries is cadmium (Cd) contamination in cacao beans. Agroforestry systems with cacao (CAFSs) improve soil health and can remediate Cd through tree phytoextraction. Effective phytoremediation requires Cd-tolerant, high-biomass species and preferential Cd allocation to stems. This study evaluated the phytoremediation potential of four forest species (Cariniana pyriformis Miers, Terminalia superba Engl. and Diels, Swietenia macrophylla King, and Cedrela odorata L.) under cadmium (Cd) exposure. C. pyriformis exhibited hypertolerance, showing minimal biomass reduction (less than 15%, changing from 1.619 to 1.343 g plant−1) under excess Cd conditions, compared to Cedrela odorata and T. superba, which showed significant biomass reductions. C. pyriformis and T. superba showed notable Cd accumulation in stems (652.99 and 635.39 mg Cd kg−1), an essential feature for wood tree-mediated phytoextraction, while C. odorata allocated more Cd to leaves (35.35 mg Cd kg−1). C. pyriformis maintained high photosynthesis (12.8 μmol CO2 m−2 s−1), light use efficiency (0.086 mol CO2 mol photons−1), and an increased relative growth rate (0.575 g g−1 day−1) under Cd exposure. Overall, C. pyriformis demonstrated significant potential for use in phytoremediation due to its high Cd tolerance (84%), efficient allocation to stems (17%), and sustained physiological performance under Cd exposure. Conversely, C. odorata allocates Cd to leaves (16%), which can reintroduce Cd into the soil, and exhibits a low tolerance index (54%) under higher cadmium contamination. Further studies are still needed to understand the specific mechanisms of Cd accumulation in stems of promising species like C. pyriformis and T. superba.